Levadura de malicia - Davies, Robertson, 1913-1995; Cardeñoso, Concha; Davies, Robertson, 1913-1995. (Barcelona, España : Libros del Asteroide S.L.U., 2012)
The following announcement appeared in the Salterton Evening Bellman: "Professor and Mrs. Walter Vambrace are pleased to announce the engagement of their daughter, Pearl Veronica, to Solomon Bridgetower, Esq., son of ..." Although the malice that prompted the insertion of this false engagement notice was aimed at three people only--Solly Bridgetower, a junior instructor in English at Waverly University; Pearl Vambrace, the subdued daughter of a domineering professor; and Gloster Ridley, the anxiety-ridden editor of the Evening Bellman--the leaven of malice will change permanently, for good or ill, the lives of many of the citizens of Salterton. Robertson Davies jumps at the opportunity this situation provides to create memorable characters and lasting impressions.
Sequel to: A merced de la tempestad.
Sequel: Una mezcla de flaquezas.
Second book of his Trilogía de Salterton.
Online resource; title from ePub title page (Digitalia, viewed March 20, 2018)
Keywords: Newspaper editors -- Fiction; Truthfulness and falsehood -- Fiction; Betrothal -- Fiction; Practical jokes -- Fiction; Salterton (Ont.) (Imaginary place) -- Fiction; Humorous fiction; Electronic books